Screening of Sugarcane Genotypes for Smut (Sporisorium scitamineum) Resistance Under Greenhouse Conditions - de Fátima Santos, Lucélia [UNESP]; da Silva, Felipe Brussolo [UNESP]; Anjos, Luciana Oliveira Souza; Raiol Júnior, Laudecir Lemos [UNESP]; dos Anjos, Ivan Antônio; de Carvalho Fernandes, Tanuza; da Silva, Marcel Fernando; Perecin, Dilermando [UNESP]; de Goes, Antônio [UNESP]; Pinto, Luciana Rossini (MDPI, 2025)
Sugarcane is one of the most economically important crops, particularly in Brazil, which is the largest sugarcane producer globally. Sugarcane smut, caused by the fungus Sporisorium scitamineum (Syd.), is a major disease of this crop. This study investigated the response of 165 sugarcane genotypes to smut infection under greenhouse conditions using the needle-bud puncture method. The disease incidence, the Area Under the Disease Progress Curve (AUDPC), and the relative Area Under the Disease Progress Curve (rAUDPC) were calculated, along with broad-sense heritability (h2) and the genotype’s effects. Spearman’s correlation coefficient (r2) was used to determine the correlation between the number of corresponding genotypes with smut incidence in both the greenhouse and the field. The incidence of smut ranged from 0% to 88%, and AUDPC values varied from 0 to 500 for 131 of the 165 genotypes. Based on the rAUDPC, 54 genotypes were classified as highly resistant. The correlation between greenhouse and field disease expression was positive and moderately strong (r² = 61%), and the h2 value in greenhouse conditions was 74%. The needle-bud puncture method combined with the rAUDPC values was promising for identifying susceptible genotypes and highlighting potential smut-resistant genotypes.
Keywords: plant disease; Saccharumspp; sugarcane breeding